Safety case: cargo cranes - Anatoly A. Korotkiy; , Elena Yegelskaya; Anatoly P. Sherstyuk (Advanced Engineering Research)
Introduction. Issues of ensuring safe operation of cranes due to changes in the legislative - regulatory system that allow for compromise solutions in case of deviations from the industrial safety requirements are considered. Materials and Methods. An example of safety risks under the crane operation taking into account the enactment of the Federal regulations to the extent of new requirements for safety zones is given. Survey data of the site operated with deviations from the industrial safety requirements are used under operation of the frame crane. The method of expert evaluation of the adverse event frequency is applied. It makes possible to develop recommendations for risk reduction. Research Results . In safety case of a hazardous industrial facility, reasonable safety management and engineering control (security barriers) are defined including data on the technological protection, blockings, and automatic protection systems. The employee qualification requirements for the safe operation of cranes are listed. Discussion and Conclusions . The results obtained are applicable to the facilities that operate cranes in order to reduce the accident risks. The safety rationale provides a clear understanding and an objective assessment of the possible accident risks and their consequences. Taking into account the data obtained, the actual working conditions can be optimized, and the problems of further safe operation can be solved.